Phenotypic detection ofT lymphocyte subsets in Bali cattle lymph nodes with malignant catarrhal fever by immunohistochemical techniques - Damayanti, Rini (Indonesian Journal of Animal and Veterinary Sciences, 1996)
A study was carried out to detect the phenotype ofT cell subsets in six Bali cattle affected with malignant catarrhal fever (MCF). This was performed by means of immunohistochemical technique using avidin-biotin-peroxidase complex methods. Seven monoclonal antibodies against lymphocyte surface antigen were used to detect T cell subsets ie . CD1, CD2, CD4, CD5, CD8, CD45, and WC 1. The results showed that the subsets were all detected either in the MCFor non-MCF infected Bali cattle lymph nodes. However, CD8 was more predominantly occupied in the MCF Bali cattle . This indicated that CD8 was a cytotouic Tlymphocytes and acted as potential mediators for immunopathological process in MCF. Â  Keywords : Malignant catarrhal fever, Tlymphocyte subsets, Bali cattle, immunohistochemical technique